Penatalaksanaan Holistik pada Lansia dengan Neurodermatitis, Infeksi Sekunder dan Obesitas melalui Pendekatan Kedokteran Keluarga di Wilayah Puskesmas Susunan Baru - Syarifatunnisa; Mayasaari, Diana (CV. Jasa Sukses Abadi, 2024)
Neurodermatitis is a chronic inflammatory skin disease characterized by symptoms of itching and thickening of the skin due to repeated scratching. Secondary infections can occur if there has been damage to skin integrity, or changes in local immune conditions due to primary skin disease followed by bacterial infection. People who are obese and who consume steroids or antibiotics are at risk of neurodermatitis. With triggers in the form of psychological stress which often occurs in adults and the elderly, because they tend to experience psychological disorders, in the form of anxiety, feelings of helplessness, and changes in body image. It is estimated to occur in around 12% of the total population. The aim of implementing Evidence Based Medicine (EBM) based family doctor services for patients is by identifying risk factors, clinical problems, and patient management based on patient problems using a patient centered and family approach. Data is obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. The assessment is carried out based on a holistic diagnosis from the beginning, process and end of the study quantitatively and qualitatively. The patient, Mrs. SU, 63 years old, has internal risks, namely elderly age, minimal knowledge, psychological stress, poor personal hygiene, and rarely exercising. Management of patients in a holistic and comprehensive manner, patient-centered, family approach, and community-based in literature based on EBM. Interventions were provided medically and non-medically in 3 visits. Based on the evaluation results, it was found that there was an increase in knowledge, changes in clean and healthy lifestyles and understanding of disease.